Determinants of Angiographic Thrombus Burden in Patients With ST-Segment Elevation Myocardial Infarction. (October 2014) - Tanboga, Ibrahim Halil; Topcu, Selim; Aksakal, Enbiya; Kalkan, Kamuran; Sevimli, Serdar; Acikel, Mahmut
Aims: We aimed to investigate the determinants of angiographic thrombus burden in patients with ST-segment elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (pPCI). Methods: The study population consisted of 662 patients with nonanemic STEMI who underwent pPCI. Clinical, laboratory, and demographic properties of the patients were recorded. Baseline hematologic indices were measured at the time of admission. Angiographic coronary thrombus burden was scored based on thrombolysis in myocardial infarction (TIMI) thrombus grades. After wiring and/or small balloon dilation, patients with thrombus burden grades 4 and 5 were defined as high thrombus burden, and patients with thrombus burden <grade 4 was defined as low thrombus burden. Result: Patients with high thrombus burden had more family history of coronary artery disease, longer pain to balloon time, higher Killip class (≥II), higher neutrophil to lymphocyte ratio, red cell distribution width (RDW), baseline creatine kinase-MB fraction (CK-MB) and baseline troponin, higher peak CK-MB, and peak troponinbut lower triglycerides. Angiographically, patients with high thrombus burden had longer lesion in the infarct-related artery, less frequent direct stenting, lower epicardial and myocardial perfusion, more frequent distal embolization, and more frequent electrocardiographic and angiographic no reflow. In multivariate logistic regression analysis, only RDW (odds ratio: 1.29, 95% confidence interval 1.19-1.39, P < .001) was determined as independent predictor. The area under the receiver–operating characteristic curve of the RDW was 0.733 (0.690-0.776, P < .001) to predict high TIMI thrombus burden. Conclusion: Present study results demonstrated that high thrombus burden in patients with STEMI was associated with impaired postprocedural epicardial and myocardial perfusion and higher no reflow and distal embolization; and increased RDW values were independent predictors of coronary thrombus burden.